Human Cognitive Ability Is Modulated by Aromatase Availability in the Brain in a Sex-Specific Manner - Alia-Klein, Nelly; Preston-Campbell, Rebecca N.; Kim, Sung Won; Pareto, Deborah; Logan, Jean; Wang, Gene-Jack; Moeller, Scott J.; Fowler, Joanna S.; Biegon, Anat (Frontiers in Neuroscience, 2020)
The enzyme aromatase catalyzes the final step in estrogen biosynthesis, converting testosterone to estradiol, and is expressed in the brain of all mammals. Estrogens are thought to be important for maintenance of cognitive function in women, whereas testosterone is thought to modulate cognitive abilities in men. Here we compare differences in cognitive performance in relation to brain aromatase availability in healthy men and women. Twenty-seven healthy participants were administered tests of verbal learning and memory and perceptual/abstract reasoning. In-vivo images of brain aromatase availability were acquired in this sample using Positron Emission Tomography (PET) with the validated aromatase radiotracer [11C]vorozole. Regions of interest were placed bilaterally on the amygdala and thalamus where aromatase availability is highest in the human brain. Though cognitive performance and aromatase availability did not differ as a function of sex, higher availability of aromatase in the amygdala was associated with lower cognitive performance in men. No such relationship was found in women; and the corresponding regression slopes were significantly different between the sexes. Thalamic aromatase availability was not significantly correlated with cognitive performance in either sex. These findings suggest that the effects of brain aromatase on cognitive performance are both region- and sex-specific, and may explain some of the normal variance seen in verbal and non-verbal cognitive abilities in men and women as well as sex differences in the trajectory of cognitive decline associated with Alzheimer’s disease.